Graphene enhanced photocuring 3D printing silicon-based ceramic as well as preparation method and application thereof
By introducing graphene and boride into the silicon-based ceramic core, the photocuring and sintering process is optimized, and the accuracy problem of the ceramic core in the curing forming and sintering shrinkage stages is solved, and high-precision silicon-based ceramic core manufacturing is achieved , improves its application performance in complex structures.
Patent Information
- Application Number
- CN202411293655.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The prior art is difficult to effectively regulate the dimensional accuracy of the silicon oxide-based ceramic core in the curing forming and sintering shrinkage stages, resulting in a decrease in the accuracy of the ceramic core, affecting its application in complex structures such as aircraft engine turbine blades.
Graphene-enhanced photocuring 3D printing of silicon-based ceramics, by adjusting the ratio of photosensitive resin and silicon-based composite ceramic powder, graphene is introduced as an accuracy regulator and an oxidation expansion agent, and combined with silicon boronide and zirconium boride as mineralization modification Properties, optimize photocuring and sintering processes, inhibit overcuring and sintering shrinkage.
The forming accuracy and sintering shrinkage of the ceramic core are significantly improved, and the high-precision additive manufacturing of silicon-based ceramic cores is realized, which enhances its application capabilities in complex structures.
Smart Images

Figure CN119143489A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic additive manufacturing, and specifically relates to a graphene-enhanced light-cured 3D-printed silicon-based ceramic and a preparation method and application thereof. Background Art
[0002] Ceramic cores are key adapters for forming complex air-cooled structures of aircraft engine turbine blades, which can effectively improve the performance of aircraft engines. Traditional ceramic core preparation processes such as hot pressing and gel injection molding rely heavily on molds, and have disadvantages such as long R&D cycles and high costs, making it difficult to form ceramic cores with complex structures. Ceramic 3D printing technology has the characteristics of no molds and excellent surface quality, and can be used for the integrated forming of ceramic cores with complex structures.
[0003] Silica-based ceramics are widely used in the field of ceramic cores due to their excellent high-temperature stability and easy removal. However, since the refractive index of silica is close to that of the photosensitive resin used for photocuring, it is easy to cause a large over-curing area, which seriously reduces the precision of the prepared ceramic blank, which is not conducive to the practical application of ceramic cores. In the subsequent degreasing and sintering process, the ceramic will produce sintering shrinkage due to densification, and the dimensional accuracy will further decrease. Patent CN117303870A discloses a photocuring additive manufacturing zero sintering shrinkage aluminum-based ceramic core material, which has significantly reduced sintering shrinkage, but does not pay attention to the influence of the curing and forming stage on the accuracy of the ceramic core. Therefore, how to regulate the dimensional accuracy of the ceramic core in the two stages of curing and forming-sintering shrinkage is the main problem facing silicon-based ceramic cores. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a graphene-enhanced photocurable 3D-printed silicon-based ceramic and a preparation method and application thereof in view of the deficiencies of the above-mentioned prior art. The method can simultaneously adjust the dimensional accuracy of the photocurable 3D-printed silicon oxide ceramic curing forming-sintering shrinkage, and obtain a silicon-based ceramic core with excellent comprehensive performance, so as to promote the application of ceramic 3D printing technology in the field of precision casting.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a graphene-enhanced light-cured 3D printed silicon-based ceramic, wherein the graphene-enhanced light-cured 3D printed silicon-based ceramic is made of the following raw materials in volume fraction: 32% to 44% of photosensitive resin, and the remainder is silicon-based composite ceramic powder;
[0006] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 70 to 90 parts of matrix material, 10 to 25 parts of mineralization modifier, 0 parts < graphene < 0.1 parts; graphene is used as a precision control agent;
[0007] The photosensitive resin is composed of the following raw materials in mass fractions: 1% to 5% of a photoinitiator, 5% to 10% of a dispersant, and the remainder being a cross-linking aid;
[0008] The matrix material is fused quartz;
[0009] The mineralization modifier is a mixture of silicon boride and zirconium boride;
[0010] The crosslinking aid is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, isobornyl acrylate and isobornyl methacrylate;
[0011] The dispersant is BYK9076, BYK111 or KOS110;
[0012] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone or trimethylbenzoyl-diphenylphosphine oxide.
[0013] Preferably, the fused silica includes fused silica in three particle size ranges: 0 μm<d1≤5 μm, 5 μm<d2≤15 μm, and 15 μm<d2≤30 μm.
[0014] Preferably, the crosslinking aid is composed of the following raw materials in parts by weight: 50 to 70 parts of 1,6-hexanediol diacrylate, 20 to 50 parts of trimethylolpropane triacrylate, 10 to 20 parts of isobornyl acrylate and 10 to 20 parts of isobornyl methacrylate.
[0015] Among them, isobornyl acrylate, isobornyl methacrylate, and 1,6-hexanediol diacrylate have a lower number of functional groups and can effectively reduce the viscosity of the ceramic slurry; trimethylolpropane triacrylate is a trifunctional organic compound that can effectively promote photopolymerization reactions and improve printing efficiency.
[0016] Preferably, the mineralization modifier is a powder with a particle size of 20 μm to 50 μm.
[0017] The present invention also provides a method for preparing the above-mentioned graphene-enhanced light-cured 3D printed silicon-based ceramics, which method is:
[0018] S1, ball milling the photosensitive resin and the silicon-based composite ceramic powder at a rotation speed of 300 rpm to 600 rpm for 3 h to 5 h to obtain a ceramic slurry that can be used for photocuring;
[0019] S2. Place the photocurable ceramic slurry obtained in S1 in a ceramic 3D printer, set the printing layer thickness to 50 μm to 150 μm, the ultraviolet light wavelength to 405 nm, the exposure time to 3 s to 5 s, and the exposure power to 10 mW / cm2 to 30 mW / cm2. 2, after printing layer by layer, a ceramic core blank is obtained;
[0020] S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.1°C / min to 0.5°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 1h to 2h, respectively, to obtain a degreased silicon-based ceramic;
[0021] S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and in an air atmosphere, heat it from room temperature to 1150°C to 1250°C at a heating rate of 0.1°C / min to 0.5°C / min, keep it warm for 4h to 8h, then cool it to 900°C at a cooling rate of 1°C / min to 4°C / min, and cool it to room temperature with the furnace to obtain graphene enhanced light-curing 3D printed silicon-based ceramics.
[0022] Preferably, the over-curing width of the graphene-enhanced light-curing 3D-printed silicon-based ceramics in S4 is -50.34 μm to 52.09 μm, the sintering shrinkage is 2.70% to 3.16%, and the porosity is 26.69% to 27.7%.
[0023] The present invention also provides an application of the above-mentioned graphene-enhanced light-curing 3D-printed silicon-based ceramics, and the graphene-enhanced light-curing 3D-printed silicon-based ceramics are used for precision casting of ceramic cores.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The present invention introduces graphene into photocuring 3D printing. Based on its excellent light absorption characteristics, it effectively improves the complex coupling effect between ultraviolet light and ceramic particles, significantly suppresses the over-curing area, and thus regulates its forming accuracy so that the size of the blank is consistent with the design size. In the sintering stage, graphene can be used as a shrinkage compensator to generate CO2 through its oxidation expansion, thereby suppressing sintering shrinkage and improving the porosity, which is helpful for the subsequent removal process and the accuracy of the turbine blades. In this way, the dimensional accuracy of the silicon-based ceramic core in the curing forming-sintering shrinkage stage can be optimized at the same time. By introducing silicon boride and zirconium boride, they are oxidized during the high-temperature sintering process to generate silicon oxide and zirconium oxide respectively. On the one hand, the generated silicon oxide can well supplement the silicon source and transform into quartz to enhance the matrix strength. On the other hand, zirconium oxide transforms from monoclinic phase to tetragonal phase at 1200°C, promotes the formation of microcracks, increases the energy loss mechanism, alleviates the stress concentration phenomenon, and better improves the fracture toughness and bending strength of the ceramic core.
[0026] 2. The over-curing of the graphene-enhanced photocurable 3D printed silicon-based ceramics prepared by the present invention tends to 0 μm, the sintering shrinkage is 2.70% to 3.16%, and the porosity is 26.69% to 27.7%. The forming-sintering dimensional changes are synergistically regulated, and high-precision additive manufacturing of silicon-based ceramic cores is achieved.
[0027] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a test chart of the photocuring accuracy in Examples 1-5 of the present invention.
[0029] Figure 2 This is a microscopic morphology of the light-cured silicon-based ceramic core prepared in Example 1 of the present invention.
[0030] Figure 3 This is a physical picture of the complex structure sample prepared by the present invention.
[0031] Figure 4 This is a diagram of the physical properties of the ceramic cores of Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0032] Example 1
[0033] The graphene-enhanced light-cured 3D-printed silicon-based ceramic of this embodiment is made of the following raw materials in volume fraction: 35% of photosensitive resin and the remainder of silicon-based composite ceramic powder;
[0034] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 90 parts of matrix material, 10 parts of mineralization modifier, and 0.0006 parts of graphene;
[0035] The photosensitive resin is composed of the following raw materials in mass fractions: 4% of photoinitiator, 8% of dispersant, and the balance of cross-linking auxiliary agent;
[0036] The matrix material is fused quartz; the fused quartz includes fused quartz of three particle size ranges with a mass ratio of 7:2:1: 0 μm<d1≤5 μm, 5 μm<d2≤15 μm, 15 μm<d2≤30 μm;
[0037] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a mass ratio of 1:1 and a particle size of 20 μm;
[0038] The crosslinking auxiliary agent is composed of the following raw materials in parts by weight: 60 parts of 1,6-hexanediol diacrylate, 20 parts of trimethylolpropane triacrylate, 10 parts of isobornyl acrylate and 10 parts of isobornyl methacrylate.
[0039] The dispersant is BYK dispersant-111 (BYK111);
[0040] The photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0041] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced light-cured 3D printed silicon-based ceramics, which is:
[0042] S1, using zirconium oxide ball milling beads as a medium, ball milling the photosensitive resin and silicon-based composite ceramic powder at a speed of 600 rpm for 4 hours to obtain a ceramic slurry that can be used for photocuring;
[0043] S2. Place the photocurable ceramic slurry obtained in S1 in a ceramic 3D printer, set the printing layer thickness to 100 μm, the UV wavelength to 405 nm, the exposure time to 5 s, and the exposure power to 15 mW / cm 2 , after printing layer by layer, a ceramic core blank is obtained;
[0044] S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.2°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 2h respectively to obtain a degreased silicon-based ceramic;
[0045] S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and heat it from room temperature to 1200°C at a heating rate of 0.2°C / min in an air atmosphere, keep it warm for 6 hours, then cool it to 900°C at a cooling rate of 2°C / min, and cool it to room temperature with the furnace to obtain graphene-enhanced light-curing 3D printed silicon-based ceramics.
[0046] The exposure performance test of the graphene enhanced light-curing 3D printed silicon-based ceramic prepared in this embodiment showed that the over-curing width was 52.09 μm. The physical property test of the obtained ceramic core showed that the shrinkage rate was 3.16% and the porosity was 24.33%.
[0047] This embodiment also provides an application of the above-mentioned graphene-enhanced light-curing 3D-printed silicon-based ceramics, wherein the graphene-enhanced light-curing 3D-printed silicon-based ceramics are used for precision casting of ceramic cores.
[0048] This embodiment can effectively adjust the forming accuracy of the photocuring additively manufactured silicon-based ceramic core and inhibit sintering shrinkage, avoid the generation of interlayer cracks during the degreasing and sintering process, and obtain a silicon-based ceramic core with excellent comprehensive performance.
[0049] like Figure 2As shown, there are a large number of pores in the microstructure of the sample, which can be attributed to the oxidation expansion of graphene, which plays the role of a pore former, improves the porosity of the ceramic core, and is beneficial to the subsequent removal process.
[0050] Comparative Example 1
[0051] The preparation method and raw materials of the 3D printed silicon-based ceramics in this comparative example are the same as those in Example 1, except that no graphene is added to the silicon-based composite ceramic powder in this comparative example.
[0052] The comparative 3D printed silicon-based ceramics were subjected to exposure performance testing, and the results showed that the over-curing width was 564.3 μm. The obtained ceramic core was subjected to physical property testing, and the results showed that the shrinkage rate was 3.56% and the porosity was 23.12%.
[0053] Based on the analysis of solidification behavior, graphene can effectively reduce the over-solidification width of the core through the light absorption effect. During the sintering process, graphene can effectively reduce the sintering shrinkage of the core through oxidation reaction and increase the porosity, which is beneficial to dimensional accuracy and also helps investment casting.
[0054] Example 2
[0055] The graphene-enhanced light-cured 3D-printed silicon-based ceramic of this embodiment is made of the following raw materials in volume fraction: 32% photosensitive resin and the remainder is silicon-based composite ceramic powder;
[0056] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 70 parts of matrix material, 25 parts of mineralization modifier, and 0.0004 parts of graphene;
[0057] The photosensitive resin is composed of the following raw materials in mass fractions: 5% photoinitiator, 10% dispersant, and the balance is cross-linking auxiliary agent;
[0058] The matrix material is fused quartz; the fused quartz includes fused quartz of three particle size ranges with a mass ratio of 7:2:1: 0 μm<d1≤5 μm, 5 μm<d2≤1 μm, and 15 μm<d2≤30 μm;
[0059] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a mass ratio of 1:1 and a particle size of 50 μm;
[0060] The crosslinking auxiliary agent is composed of the following raw materials in parts by weight: 50 parts of 1,6-hexanediol diacrylate, 30 parts of trimethylolpropane triacrylate, 20 parts of isobornyl acrylate and 20 parts of isobornyl methacrylate.
[0061] The dispersant is BYK9076 dispersant;
[0062] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0063] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced light-cured 3D printed silicon-based ceramics, which is:
[0064] S1, using zirconium oxide ball milling beads as a medium, ball milling the photosensitive resin and silicon-based composite ceramic powder at a speed of 300 rpm for 5 hours to obtain a ceramic slurry that can be used for photocuring;
[0065] S2. Place the photocurable ceramic slurry obtained in S1 in a ceramic 3D printer, set the printing layer thickness to 150 μm, the UV wavelength to 405 nm, the exposure time to 5 s, and the exposure power to 30 mW / cm 2 , after printing layer by layer, a ceramic core blank is obtained;
[0066] S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.1°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 1 hour respectively to obtain a degreased silicon-based ceramic;
[0067] S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and heat it from room temperature to 1150°C at a heating rate of 0.1°C / min in an air atmosphere, keep it warm for 8 hours, then cool it to 900°C at a cooling rate of 1°C / min, and cool it to room temperature with the furnace to obtain graphene-enhanced light-curing 3D printed silicon-based ceramics.
[0068] The over-curing width of the graphene-enhanced light-cured 3D-printed silicon-based ceramic prepared in this embodiment is 13.58 μm, the sintering shrinkage is 3.04%, and the porosity is 26.80%.
[0069] This embodiment also provides an application of the above-mentioned graphene-enhanced light-curing 3D-printed silicon-based ceramics, wherein the graphene-enhanced light-curing 3D-printed silicon-based ceramics are used for precision casting of ceramic cores.
[0070] Example 3
[0071] The graphene-enhanced light-cured 3D-printed silicon-based ceramic of this embodiment is made of the following raw materials in volume fraction: 44% photosensitive resin and the remainder is silicon-based composite ceramic powder;
[0072] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 80 parts of matrix material, 20 parts of mineralization modifier, and 0.0002 parts of graphene;
[0073] The photosensitive resin is composed of the following raw materials in mass fractions: 1% photoinitiator, 5% dispersant, and the balance is cross-linking auxiliary agent;
[0074] The matrix material is fused quartz; the fused quartz includes fused quartz of three particle size ranges with a mass ratio of 7:2:1: 0 μm<d1≤5 μm, 5 μm<d2≤1 μm, and 15 μm<d2≤30 μm;
[0075] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a mass ratio of 1:1 and a particle size of 20 μm;
[0076] The crosslinking auxiliary agent is composed of the following raw materials in parts by weight: 70 parts of 1,6-hexanediol diacrylate, 50 parts of trimethylolpropane triacrylate, 15 parts of isobornyl acrylate and 15 parts of isobornyl methacrylate.
[0077] The dispersant is Guangzhou Kang Oushuang Trading Co., Ltd. product-110 (KOS110);
[0078] The photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0079] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced light-cured 3D printed silicon-based ceramics, which is:
[0080] S1, using zirconium oxide ball milling beads as a medium, ball milling the photosensitive resin and silicon-based composite ceramic powder at a speed of 500 rpm for 4 hours to obtain a ceramic slurry that can be used for photocuring;
[0081] S2, placing the ceramic slurry that can be used for photocuring obtained in S1 in a ceramic 3D printer, setting the printing layer thickness to 50 μm, the ultraviolet light wavelength to 405 nm, the exposure time to 3 s, and the exposure power to 10 mW / cm, and obtaining a ceramic core blank after layer-by-layer printing;
[0082] S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.5°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 2h respectively to obtain a degreased silicon-based ceramic;
[0083] S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and heat it from room temperature to 1250°C at a heating rate of 0.5°C / min in an air atmosphere, keep it warm for 4 hours, then cool it to 900°C at a cooling rate of 4°C / min, and cool it to room temperature with the furnace to obtain graphene-enhanced light-curing 3D printed silicon-based ceramics.
[0084] The over-curing width of the graphene-enhanced light-cured 3D-printed silicon-based ceramic prepared in this embodiment is 2.79 μm, the sintering shrinkage is 2.77%, and the porosity is 26.69%.
[0085] The graphene-enhanced light-curing 3D-printed silicon-based ceramics prepared in this embodiment are used for precision casting of ceramic cores.
[0086] Example 4
[0087] The graphene-enhanced light-cured 3D-printed silicon-based ceramic of this embodiment is made of the following raw materials in volume fraction: 40% photosensitive resin and the remainder silicon-based composite ceramic powder;
[0088] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 75 parts of matrix material, 20 parts of mineralization modifier, and 0.0001 parts of graphene;
[0089] The photosensitive resin is composed of the following raw materials in mass fractions: 4% of photoinitiator, 8% of dispersant, and the balance of cross-linking auxiliary agent;
[0090] The matrix material is fused quartz; the fused quartz includes fused quartz of three particle size ranges with a mass ratio of 5:4:1: 0 μm<d1≤5 μm, 5 μm<d2≤1 μm, and 15 μm<d2≤30 μm;
[0091] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a mass ratio of 1:2 and a particle size of 20 μm;
[0092] The crosslinking auxiliary agent is composed of the following raw materials in parts by weight: 50 parts of 1,6-hexanediol diacrylate, 30 parts of trimethylolpropane triacrylate, 10 parts of isobornyl acrylate and 10 parts of isobornyl methacrylate.
[0093] The dispersant is BYK-111 (BYK111);
[0094] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0095] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced light-cured 3D printed silicon-based ceramics, which is:
[0096] S1, using zirconium oxide ball milling beads as a medium, ball milling the photosensitive resin and silicon-based composite ceramic powder at a speed of 600 rpm for 5 hours to obtain a ceramic slurry that can be used for photocuring;
[0097] S2. Place the photocurable ceramic slurry obtained in S1 in a ceramic 3D printer, set the printing layer thickness to 100 μm, the UV wavelength to 405 nm, the exposure time to 4 s, and the exposure power to 30 mW / cm 2 , after printing layer by layer, a ceramic core blank is obtained;
[0098] S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.4°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 1 hour respectively to obtain a degreased silicon-based ceramic;
[0099] S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and heat it from room temperature to 1180°C at a heating rate of 0.4°C / min in an air atmosphere, keep it warm for 5 hours, then cool it to 900°C at a cooling rate of 3°C / min, and cool it to room temperature with the furnace to obtain graphene-enhanced light-curing 3D printed silicon-based ceramics.
[0100] The over-curing width of the graphene-enhanced light-cured 3D-printed silicon-based ceramic prepared in this embodiment is -25.28 μm, the sintering shrinkage is 2.72%, and the porosity is 27.39%.
[0101] The graphene-enhanced light-curing 3D-printed silicon-based ceramics prepared in this embodiment are used for precision casting of ceramic cores.
[0102] Example 5
[0103] The graphene-enhanced light-cured 3D-printed silicon-based ceramic of this embodiment is made of the following raw materials in volume fraction: 42% photosensitive resin and the remainder is silicon-based composite ceramic powder;
[0104] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 85 parts of matrix material, 16 parts of mineralization modifier, and 0.0001 parts of graphene;
[0105] The photosensitive resin is composed of the following raw materials in mass fractions: 4% of photoinitiator, 8% of dispersant, and the balance of cross-linking auxiliary agent;
[0106] The matrix material is fused quartz; the fused quartz includes fused quartz of three particle size ranges with a mass ratio of 6:3:1: 0 μm<d1≤5 μm, 5 μm<d2≤1 μm, and 15 μm<d2≤30 μm;
[0107] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a mass ratio of 1:3 and a particle size of 20 μm;
[0108] The crosslinking auxiliary agent is composed of the following raw materials in parts by weight: 600 parts of 1,6-hexanediol diacrylate, 300 parts of trimethylolpropane triacrylate, 12 parts of isobornyl acrylate and 10 parts of isobornyl methacrylate.
[0109] The dispersant is BYK-111;
[0110] The photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0111] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced light-cured 3D printed silicon-based ceramics, which is:
[0112] S1, using zirconium oxide ball milling beads as a medium, ball milling the photosensitive resin and silicon-based composite ceramic powder at a speed of 600 rpm for 5 hours to obtain a ceramic slurry that can be used for photocuring;
[0113] S2. Place the photocurable ceramic slurry obtained in S1 in a ceramic 3D printer, set the printing layer thickness to 60 μm, the UV wavelength to 405 nm, the exposure time to 4 s, and the exposure power to 112 mW / cm 2 , after printing layer by layer, a ceramic core blank is obtained;
[0114] S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.3°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 1 h respectively to obtain a degreased silicon-based ceramic;
[0115] S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and heat it from room temperature to 1200°C at a heating rate of 0.3°C / min in an air atmosphere, keep it warm for 6 hours, then cool it to 900°C at a cooling rate of 2°C / min, and cool it to room temperature with the furnace to obtain graphene-enhanced light-curing 3D printed silicon-based ceramics.
[0116] The over-curing width of the graphene-enhanced light-cured 3D-printed silicon-based ceramic prepared in this embodiment is -50.34 μm, the sintering shrinkage is 2.70%, and the porosity is 26.80%.
[0117] The graphene-enhanced light-curing 3D-printed silicon-based ceramics prepared in this embodiment are used for precision casting of ceramic cores.
[0118] like Figure 1As shown in the figure, (a) to (e) are optical microscope images of samples with graphene contents of 0.2‰, 0.4‰, 0.6‰, 0.8‰, and 1.0‰, respectively. The red arrow indicates the over-curing width of the sample. As the graphene content increases from 0.2‰ to 1‰, the over-curing width gradually decreases from 52.09μm to -50.34μm. As the graphene content exceeds 0.6‰, the contour of the cured sample gradually becomes jagged, and holes appear inside. This shows that photocuring is significantly inhibited.
[0119] like Figure 3 As shown, (a) shows the influence of graphene on the macroscopic morphology of the test rod, (b) shows the designed model and complex structure model, indicating that graphene can realize the preparation of complex samples, (c) is the SEM image of the complex sample, indicating that the actual size is consistent with the designed size, and (d) is the energy spectrum, indicating that various elements are evenly distributed inside the sample. Figure 3 The samples prepared with a graphene content of 0.6‰ were displayed, and the macroscopic morphology of the samples without graphene was compared. The sample was clearly observed to be warped, which was due to the internal stress concentration caused by photocuring. The addition of graphene can effectively alleviate this phenomenon and significantly improve the dimensional accuracy of the sample. The size of the complex structure sample was measured by SEM, which was consistent with the design model, indicating that the addition of graphene can achieve the preparation of high-precision ceramic cores.
[0120] like Figure 4 As shown, Figure 4 (a) shows the effect of different amounts of graphene on porosity and packing density. As the amount of graphene increases, the apparent porosity of the ceramic core increases from 24.33% to 27.72%. On the contrary, the packing density increases from 1.75 g / cm 3 Down to 1.65g / cm 3 The main reason for this phenomenon is the oxidation reaction of graphene, which produces CO2, improves the porosity inside the core, and leads to a decrease in packing density. The addition of graphene leads to a gradual increase in the bending strength of the ceramic core ( Figure 4 (b)), it increased from 10.48MPa to 13.97MPa, and then decreased slightly to 13.53MPa. This can be explained by the fact that the ceramic slurry containing 0.2‰ graphene has a larger S d, which enables the same curing depth to be achieved at relatively low exposure energies. Therefore, weak interlayer bonding usually leads to interlayer cracking and decreased bending strength. It is worth noting that with the increase in graphene dosage, the porosity and bending strength also increase simultaneously. This is attributed to the fact that when the graphene content is low, the main factor affecting the bending strength is the internal defects caused by weak interlayer bonding during the curing process. However, as the graphene content gradually increases, the increase in apparent porosity affects the strength of the core, resulting in a slight decrease in the strength of the core. When the graphene content is 0.2‰, the high-temperature bending strength of the fiber core is limited to only 8.64MPa. This is mainly caused by thermal stress, which leads to intensified interlayer crack rupture. With the increase in interlayer bonding, the high-temperature bending strength reaches a stable level of around 16MPa. Figure 4 (c) Describes the effect of graphene dosage on the sintering shrinkage of the ceramic core. The sintering shrinkage decreases with increasing graphene content, which can be attributed to the volume expansion effect caused by graphene oxidation. The shrinkage is much higher in the Z axis (i.e., printing direction) compared to the X and Y axes. This is attributed to the technical characteristics of the VPP-3D layer-by-layer printing process, which leads to the formation of interlayer gaps, thereby exacerbating the shrinkage. The high-temperature creep resistance of the ceramic core is essential and is closely related to the dimensional accuracy of the turbine blade. Figure 4 (d) shows the effect of graphene dosage on the deformation of ceramic cores at high temperatures. As the graphene content increases, the high-temperature deflection of the ceramic core shows an initial decrease and then an increase trend. Due to the high solid loading in the ceramic slurry, the core with low graphene content does not deflect significantly at high temperatures despite the presence of cracks between the layers. As the graphene content increases, the deflection initially decreases to 1.46mm and then gradually reaches 1.63mm. The increase in deflection can be attributed to the increase in apparent porosity, which leads to a decrease in the effective load-bearing area within the ceramic, thereby causing an increase in creep.
[0121] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A graphene-enhanced light-curing 3D printing silicon-based ceramic, characterized in that: The graphene-enhanced light-curing 3D-printed silicon-based ceramic is made of the following raw materials in volume fraction: 32% to 44% photosensitive resin and the remainder is silicon-based composite ceramic powder; The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 70 to 90 parts of matrix material, 10 to 25 parts of mineralization modifier, and 0 part <0.1 part of graphene; The photosensitive resin is composed of the following raw materials in mass fractions: 1% to 5% of a photoinitiator, 5% to 10% of a dispersant, and the remainder being a cross-linking aid; The matrix material is fused quartz; The mineralization modifier is a mixture of silicon boride and zirconium boride; The crosslinking aid is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, isobornyl acrylate and isobornyl methacrylate; The dispersant is BYK9076, BYK111 or KOS110; The photoinitiator is 1-hydroxycyclohexyl phenyl ketone or trimethylbenzoyl-diphenylphosphine oxide.
2. The graphene-enhanced light-curing 3D printing silicon-based ceramic according to claim 1, characterized in that: The fused quartz includes fused quartz with three particle size ranges: 0 μm<d1≤5 μm, 5 μm<d2≤15 μm, and 15 μm<d2≤30 μm.
3. The graphene-enhanced light-curing 3D printing silicon-based ceramic according to claim 1, characterized in that: The crosslinking auxiliary agent is composed of the following raw materials in parts by weight: 50 to 70 parts of 1,6-hexanediol diacrylate, 20 to 50 parts of trimethylolpropane triacrylate, 10 to 20 parts of isobornyl acrylate and 10 to 20 parts of isobornyl methacrylate.
4. The graphene-enhanced light-curing 3D printing silicon-based ceramic according to claim 1, characterized in that: The mineralization modifier is a powder with a particle size of 20 μm to 50 μm.
5. A method for preparing the graphene-enhanced light-cured 3D printed silicon-based ceramics according to any one of claims 1 to 4, characterized in that: The method is: S1, ball milling the photosensitive resin and the silicon-based composite ceramic powder at a rotation speed of 300 rpm to 600 rpm for 3 h to 5 h to obtain a ceramic slurry that can be used for photocuring; S2. Place the photocurable ceramic slurry obtained in S1 in a ceramic 3D printer, set the printing layer thickness to 50 μm to 150 μm, the ultraviolet light wavelength to 405 nm, the exposure time to 3 s to 5 s, and the exposure power to 10 mW / cm2 to 30 mW / cm2. 2 , after printing layer by layer, a ceramic core blank is obtained; S3, placing the ceramic core blank obtained in S2 in a muffle furnace for degreasing treatment, heating from room temperature at a heating rate of 0.1°C / min to 0.5°C / min in an air atmosphere, and keeping the temperatures at 200°C, 431°C, 508°C, and 600°C for 1h to 2h, respectively, to obtain a degreased silicon-based ceramic; S4. Place the degreased silicon-based ceramic obtained in S3 in a sintering furnace, and in an air atmosphere, heat it from room temperature to 1150°C to 1250°C at a heating rate of 0.1°C / min to 0.5°C / min, keep it warm for 4h to 8h, then cool it to 900°C at a cooling rate of 1°C / min to 4°C / min, and cool it to room temperature with the furnace to obtain graphene enhanced light-curing 3D printed silicon-based ceramics.
6. The method according to claim 5, characterized in that The over-curing width of the graphene-enhanced light-curing 3D-printed silicon-based ceramics described in S4 is -50.34 μm to 52.09 μm, the sintering shrinkage is 2.70% to 3.16%, and the porosity is 26.69% to 27.7%.
7. An application of graphene-enhanced photocurable 3D printing silicon-based ceramics prepared by the preparation method as claimed in claim 5, characterized in that: The graphene-enhanced light-curing 3D-printed silicon-based ceramic is used for ceramic core precision casting.
Citation Information
Patent Citations
Zero-sintering-shrinkage aluminum-based ceramic core material for photocuring additive manufacturing
CN117303870A
Graphene-reinforced aluminum oxide-based ceramic core and preparation method thereof
CN109467419A
Graphene reinforced ceramic matrix composite material and preparation method thereof
CN110698198A
Phase-change aggregate for self-sensing and self-cooling of asphalt pavement and preparation method thereof
CN110950564A
Photocuring 3D printing manufacturing method of high-porosity ceramic core
CN112608136A
